PEMAHAMAN PESERTA PEMBEKALAN GURU KELAS/AGAMA DALAM MATA PELAJARAN PENJAS TERHADAP PENDIDIKAN JASMANI SD DI DAERAH ISTIMEWA YOGYAKARTA (DIY) - Agus Susworo Dwi Marhaendro (Jurnal Pendidikan Jasmani Indonesia, 2008)
The aim of this research is to reveal a description on the participants understanding of teaching learning process in elementary physical education on the cognitive, affective, and psychomotor aspects. They were the participants of training for classroom/ religion teachers in Yogyakarta Special Province. The population was 80 classroom/ religion teachers who participated in the training of 2005. The sample was 60 teachers taken by purposive sampling procedures. This research employed descriptive approach using questionnaire as the data collection technique. The results showed that for cognitive aspect, it was 91, 67% of cognitive aspect categorized as high, 8,33% as medium, and 0% as low. It was 6,7 %of affective aspect categorized as high, 5 % as medium, and 18,33 % as low. It was 63,33% of psychomotor aspect categorized as high, 36,67% as medium, and 0% as low. The total of those three aspects showed that the understanding of the training participants were 43,33% included as high category, 56,67% included as medium category, and 0% included as low category. Kata kunci: Pemahaman, Guru Kelas/Agama SD, Pembelajaran Pendidikan Jasmani